Balkan Pathologies of Modernity: The National Question between Consensus and Conflict - Grujic, Vanja (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The possibility of thinking and criticising modernity and modern law lies at the heart of this work. Hegel’s works firstly focus on the word ‘modern’, while the oeuvre of Jürgen Habermas offers another goal and possibility for the modern world – intersubjectivity. The world is social, but can the modern world grasp the intersubjective nature of our societies? This work follows Habermas’s arguments, and it is on the basis of their shortcomings that its criticism of modernity arises, a criticism that is focused around the theory of Carl Schmitt, which challenges the concepts of liberal democracy, legitimacy and legality, leaving us the door open to rethink the ideas and pillars of liberal democracy and its laws.Vanja Grujić is a postdoctoral researcher in the fields of law, and political and legal philosophy at the University of Brasília.